1976
DOI: 10.1017/s0022172400055790
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cigarette smoking on susceptibility to epidemic influenza and on serological responses to live attenuated and killed subunit influenza vaccines

Abstract: SUMMARYThe effects of cigarette smoking on the incidence of epidemic influenza and on the serological response to influenza vaccination with killed subunit and live attenuated vaccines have been investigated during comparative vaccine trials in Western Australia. It was found that cigarette smokers with no pre-epidemic haemagglutination-inhibiting (HI) antibody (titres of < 12) were significantly more susceptible to epidemic influenza than non-smokers. Smokers were no more susceptible however, if they had poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
38
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 24 publications
4
38
0
Order By: Relevance
“…Despite the limitations in interpreting the data presented in this study to what happens in smokers due to species-specific variables such as genetic, allometry, and metabolism, our in vivo observations together with the decreased humoral Ab response reported in vaccinated smokers (7)(8)(9) indicate that exposure to nicotine could have significant and potentially adverse effects on the vaccination efficacy of a number of vaccines currently on the market and on experimental vaccines in the pipeline. Finally, this study lays the groundwork to test remedial strategies to correct the nicotineinduced defects in the DC system and improve vaccine efficacy through the use of immunological adjuvants.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Despite the limitations in interpreting the data presented in this study to what happens in smokers due to species-specific variables such as genetic, allometry, and metabolism, our in vivo observations together with the decreased humoral Ab response reported in vaccinated smokers (7)(8)(9) indicate that exposure to nicotine could have significant and potentially adverse effects on the vaccination efficacy of a number of vaccines currently on the market and on experimental vaccines in the pipeline. Finally, this study lays the groundwork to test remedial strategies to correct the nicotineinduced defects in the DC system and improve vaccine efficacy through the use of immunological adjuvants.…”
Section: Discussionmentioning
confidence: 69%
“…The observed immunosuppression in smokers combined with the importance of DCs in maintaining immunity led us to study whether the biological activities of DCs are severely affected by exposure to nicotine. Our pioneering in vitro work (18)(19)(20)(21) revealed the nicotine-induced defects in the differentiation and biological activities of both human and mouse DCs differentiated ex vivo, particularly the ability to prime effector memory T cells as a possible mechanism for the depressed immune response reported in vaccinated smokers (7)(8)(9). In this study, we report that exposure to nicotine significantly diminishes the development of Ag-specific effector memory Th1 cells and Ab production, leading to poor host response to an otherwise protective and therapeutic vaccine.…”
mentioning
confidence: 99%
“…Associations between psychosocial factors and antibody response could be driven by variations in unhealthy behaviours, such as alcohol consumption, smoking and decreased time spent exercising, which have been associated with exposure to stress (Heslop, Davey Smith, Carroll, Macleod, Hyland & Hart, 2001) and vaccination response (Gluckman, Dvorak & MacGregor, 1977;MacKenzie, MacKenzie & Holt, 1976). In order to be able to test whether or not association between psychosocial factors and the antibody response were attributable to variations in health behaviours in the present study, these behaviours were assessed at the baseline session for the previous year using a questionnaire adapted from the Whitehall II study (Marmot, Davey-Smith, Stansfield, Patel, North, Head, White, Brunner & Feeney, 1991).…”
Section: Health Behavioursmentioning
confidence: 99%
“…In addition, high levels of alcohol consumption have been linked to reduced vaccine efficacy [61] and alcoholics have been shown to have poorer responses to some serotypes of the pneumococcal vaccine than non-alcoholic controls [62]. Similarly, cigarette smoking has been linked to reduced response to influenza [63,64], and hepatitis B vaccinations [65][66][67]. It has also been suggested that nutritional status may influence vaccine efficacy; supplementation with zinc, selenium [68], and vitamin E [69] improved the response to influenza vaccination in institutionalised elderly participants.…”
Section: Indirect Mechanismsmentioning
confidence: 99%